Critical thinking - Bastos, Maria da Ascensão Afonso (2012)
YouTube, in parallel with Moodle forums, emerge as new learning environments, fostering a multifaceted and integrated process consistent with young digital natives’ profile and the challenges demanded by a knowledge-based society. A case study was conducted in English as a second language (ESL), involving eleventh-grade secondary education students in formal and non-formal learning environments, offline and online. The research focussed on the educational value of digital video and Moodle forum discussions and their effective contribution to a meaningful and in-depth learning, aiming to develop critical thinking skills. First phase results showed that not only were a vast majority of learners not aware of many of the skills involved in critical thinking, but clear intellectual standards inherent to disciplined and critical thinking did not govern them as well. Final results showed major differences regarding learners’ achievements, indicating that YouTube and Moodle have promoted the development of critical thinking in English (ESL). In this paper we present: (a) theories that support the integration of digital videos for developing essential skills to the learning process; (b) new insights into the way foreign language may be processed; (c) methodologies with YouTube and Moodle in the educational context.